Black carbon and inorganic aerosols in Arctic snowpack - Mori, Tatsuhiro; Goto-Azuma, Kumiko; Kondo, Yutaka; Ogawa-Tsukagawa, Yoshimi; Miura, Kazuhiko; Hirabayashi, Motohiro; Oshima, Naga; Koike, Makoto; Kupiainen, Kaarle; Moteki, Nobuhiro; Ohata, Sho; Sinha, P.R.; et al. (Journal of Geophysical Research: Atmospheres, 2022)
Key Points: • First ever measurements with a high‐accuracy single‐particle soot photometer of black carbon (BC) concentrations in Arctic snowpack • Topography and BC emission flux strongly influenced latitudinal variations of mass concentrations and size distributions of BC • Measured BC mass concentrations 2–25 times lower than previously reported show the importance of revalidating climate models Black carbon (BC) deposited on snow lowers its albedo, potentially contributing to warming in the Arctic. Atmospheric distributions of BC and inorganic aerosols, which contribute directly and indirectly to radiative forcing, are also greatly influenced by depositions. To quantify these effects, accurate measurement of the spatial distributions of BC and ionic species representative of inorganic aerosols (ionic species hereafter) in snowpack in various regions of the Arctic is needed, but few such measurements are available. We measured mass concentrations of size-resolved BC (CMBC) and ionic species in snowpack by using a single-particle soot photometer and ion chromatography, respectively, over Finland, Alaska, Siberia, Greenland, and Spitsbergen during early spring in 2012–2016. Total BC mass deposited per unit area (DEPMBC) during snow accumulation periods was derived from CMBC and snow water equivalent (SWE). Our analyses showed that the spatial distributions of anthropogenic BC emission flux, total precipitable water, and topography strongly influenced latitudinal variations of CMBC, BC size distributions, SWE, and DEPMBC. The average size distributions of BC in Arctic snowpack shifted to smaller sizes with decreasing CMBC due to an increase in the removal efficiency of larger BC particles during transport from major sources. Our measurements of CMBC were lower by a factor of ~13 than previous measurements made with an Integrating Sphere/Integrating Sandwich spectrophotometer due mainly to interference from coexisting non-BC particles such as mineral dust. The SP2 data presented here will be useful for ...